Dampak stigma masyarakat tentang kelurahan penatoi sebagai "Kampung Teroris" - Firdaus Firdaus; Yayu Rahmawati Mayangsari (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
This study aims to determine the impact of the community's stigma about Penatoi Village as a "terrorist village". This research use desciptive qualitative approach. This research was conducted in the village of Penatoi, Mpunda District, Bima City. Informant selected purposively and selected based on the criteria of informants that have been made. Data analysis techniques were carried out in stages including reduction, display and drawing conclusions. Based on the results of the research, it can be concluded that the Impact of Community Stigma About Penatoi Village as a "Terrorist Village" greatly influences people's lives in Penatoi Village, this can be seen from three aspects, namely deviant self-concept, social exclusion and involvement in deviant groups. Of the three aspects above, what the people of Penatoi Village feel the most is social exclusion. Penatoi residents in their social interactions experience social exclusion which makes them ridiculed, discriminated against, even to the point of being ostracized from social interactions. If this is not minimized, it will result in negative reactions that lead to physical or verbal violence. In addition, someone who cannot accept this stigma can become a quiet, withdrawn person and can withdraw from the social environment because they feel ostracized. The bad influence or negative stigma of the Penatoi sub-district as a radical/terrorism village is very influential, how come there are many young Penatoi who have taken the police and military tests which are of particular concern to the organizing committee not to be passed, then if there are tattooists traveling outside the area and when asked where they come from and answer from Penatoi, the answer will be 'oh that's a terrorist village, yeah'. Penatoi residents feel discriminated against in the social environment, for example in the lecture environment, moreover I wear a veil so I am often ridiculed as a terrorist. The existence of these issues makes me insecure and inferior.